2015
DOI: 10.1038/ncomms8269
|View full text |Cite
|
Sign up to set email alerts
|

The optoelectronic role of chlorine in CH3NH3PbI3(Cl)-based perovskite solar cells

Abstract: Perovskite photovoltaics offer a compelling combination of extremely low-cost, ease of processing and high device performance. The optoelectronic properties of the prototypical CH3NH3PbI3 can be further adjusted by introducing other extrinsic ions. Specifically, chlorine incorporation has been shown to affect the morphological development of perovksite films, which results in improved optoelectronic characteristics for high efficiency. However, it requires a deep understanding to the role of extrinsic halide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
373
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(392 citation statements)
references
References 50 publications
18
373
1
Order By: Relevance
“…Later, chlorine incorporation was investigated to also improve the film crystallinity and provide a stable morphology as well as a better coverage in PVSCs 52. In addition, Cl incorporation was found to enhance the lifetime of the photoexcited species 53. However, experimental evidence for the presence of chloride in the perovskite films is less than 4% 54.…”
Section: Perovskite Layermentioning
confidence: 98%
“…Later, chlorine incorporation was investigated to also improve the film crystallinity and provide a stable morphology as well as a better coverage in PVSCs 52. In addition, Cl incorporation was found to enhance the lifetime of the photoexcited species 53. However, experimental evidence for the presence of chloride in the perovskite films is less than 4% 54.…”
Section: Perovskite Layermentioning
confidence: 98%
“…[11,[60][61][62] Yet the exact role chloride actually plays has been rather puzzling: while earlier reports suggested doping effects [63] that could explain the longer charge carrier diffusion lengths, finding chloride in the final perovskite films has been rather challenging. [11,62,64,65] Chloride seems to have mainly an effect on the crystal growth, as was suspected previously, [11,63] and it has since been shown that it is released together with excess MA during film annealing, or, in general, that it can facilitate the release of excess organic compounds. [62,66] Binek et al [67] showed that MAPbCl 3 crystallizes directly after the deposition of the starting solution, thus acting as a template for the formation of the desired iodide-based perovskite via a slow halide exchange from the iodide-rich environment.…”
Section: Role Of Chloride Ionsmentioning
confidence: 99%
“…100 Most publications conclude that the crystallite size of MAPbI 3 is on the order of 25-75 nm. [101][102][103][104] But these estimates may be affected by broadening factors (e.g., microstrain). Other studies arrived at a crystallite size on the order of 1.5 μm, which is questionable, given that the resolution of common lab-based XRD instruments is not capable of measuring diffraction peaks this sharp.…”
Section: Analysis Of Thin Filmsmentioning
confidence: 99%